The Impact of 3D Geometry Assisted 6E Instructional Model to Improve 3D Geometry Thinking Skills of Junior High School Students - Sudirman, Sudirman; Kusumah, Yaya Sukjaya; Martadiputra, Bambang Avip Priatna (Jurnal Pendidikan MIPA, 2022)
This study aims to reveal the impact of the 6E Instructional 3D geometry model (6E I3DGM) design in improving students' 3D geometric thinking skills. The approach in this study uses a mixed approach. The reason for choosing this approach is that researchers want to get a more comprehensive understanding of this research problem. In this study, the participants involved in this study were (1) junior high school mathematics teachers; (2) grade VIII junior high school students in one of the public junior high schools in Indramayu Regency. In addition, there are three methods of collecting data in this study, namely observation, documentation, tests, which were analyzed using qualitative and quantitative data analysis. Qualitative data analysis using Miles and Huberman (2014) modification consists of data collection, data reduction (data reduction), data display (data display), and conclusion drawing (verification). The statistical test used in this study used an independent t-test. The results of this study conclude that the 6E I3DGM design can improve students' 3D geometric thinking skills. This is because students (1) can activate students' prior knowledge; (2) can relate previous knowledge with prior knowledge; (3) can explore 3D geometry problems; (4) can facilitate the process of constructing new concepts of 3D geometry into students' memory; (5) able to elaborate 3D geometry knowledge acquired in other contexts; (6) can evaluate the acquired knowledge in order that the 3D geometry knowledge possessed by students is stored in cognitive structures for a long period of time.Keywords: 6E instructional 3D geometry model, 3D geometry thinking skills, junior high school students DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp45-56